2005
DOI: 10.2486/indhealth.43.285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pesticides on the Peripheral and Central Nervous System in Tobacco Farmers in Malaysia: Studies on Peripheral Nerve Conduction, Brain-Evoked Potentials and Computerized Posturography

Abstract: We examined the effects of pesticides on the central and peripheral nervous system in the setting of a tobacco farm at a developing country. Maximal motor and sensory nerve conduction velocities (MCV and SCV, respectively) in the median, sural and tibial nerves, postural sway, and brain-evoked potentials (auditory event-related and visual-evoked potentials) were measured in 80 male tobacco farmers and age-and sex-matched 40 controls in Kelantan, Malaysia. Median SCV (finger-wrist) in farmers using Delsen (manc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
(57 reference statements)
1
22
0
1
Order By: Relevance
“…In order to prevent health effects of exposure to pesticides it is critically important to make protective equipment and hand washing facilities available to all tobacco farm workers (Curwin et al 2003). Pesticide sprayers have an increased risk of suffering from transient neurological and psychological conditions explained by the toxicity to the peripheral and central nervous system (Kimura et al 2005;Salvi et al 2003). Pesticides used in tobacco plantations are not specific to tobacco and are therefore not regarded as an issue of this literature review.…”
Section: Pesticide Exposurementioning
confidence: 99%
“…In order to prevent health effects of exposure to pesticides it is critically important to make protective equipment and hand washing facilities available to all tobacco farm workers (Curwin et al 2003). Pesticide sprayers have an increased risk of suffering from transient neurological and psychological conditions explained by the toxicity to the peripheral and central nervous system (Kimura et al 2005;Salvi et al 2003). Pesticides used in tobacco plantations are not specific to tobacco and are therefore not regarded as an issue of this literature review.…”
Section: Pesticide Exposurementioning
confidence: 99%
“…However, it should be noted that the objective of the study was not to assess the prevalence of neurological diseases among two groups of Indiana farmers; the aim was rather to observe whether the intensity and frequency of symptoms were different in these two categories of farmers, which would allow the gathering of preliminary data for future epidemiological study. For instance, several studies on farmers exposed to agrochemicals demonstrated reduced cholinesterase activity and nerve conduction velocity [37,38], suggesting that future survey studies should be complemented by biochemical assessment, including biomarkers of exposures and health effects and clinical examinations of nervous system and mental health outcomes. Another limitation was the lack of data related to participants' gender.…”
Section: Discussionmentioning
confidence: 99%
“…These results were also identified among Malaysian tobacco farmers exposed to such substances, whose nerve conduction velocity and postural oscillations appeared to be a sensitive indicator of the effects of pesticides. 38 Regarding the toxicological group, most products used by growers do not belong to the type I, or highly toxic group. A survey found that 8% of pesticides used on crops are extremely toxic (class I), 17% are highly toxic (class II), 50% moderately toxic (Class III) and 25% low toxicity (Class IV).…”
Section: (To Be Continued) (Continuation)mentioning
confidence: 99%